Effects of Bothrops asper snake venom on the expression of cyclooxygenases and production of prostaglandins by peritoneal leukocytes in vivo, and by isolated neutrophils and macrophages in vitro - Moreira, Vanessa (2009)
In this study, the ability of Bothrops asper snake venom (BaV) to increase the production of prostaglandins PGE2 and PGD2 was assessed in a mouse model in vivo and in inflammatory cells in vitro. In addition, the expressions of COX-1 and COX-2 were assessed. BaV induced an increment in the in vivo synthesis of PGE2 and PGD2, together with an enhanced expression of COX-2, but not of COX-1. However, enzymatic activities of COX-1 and COX-2 were increased. Incubation of isolated macrophages and neutrophils with a sub-cytotoxic concentration of BaV in vitro resulted in increased release of PGE2 and PGD2 by macrophages and PGE2 by neutrophils, concomitantly with an increment in the expression of COX-2, but not of COX-1 by both cell types. Our results demonstrate the ability of BaV to promote the expression of COX-2 and to induce the synthesis of proinflammatory prostaglandins. Macrophages and neutrophils may be important targets for this venom under in vivo situation.